Organizational culture enabler and inhibitor factors for ambidextrous innovation - Mohammad AlSaied; Patrick McLaughlin (Administrative Sciences, 2024)
Ambidextrous innovation is considered to be a key framework for innovation that offers organizations the ability to maintain their current level of competitiveness and develop and sustain a long-term competitive advantage. However, the implementation of ambidextrous innovation is constrained by an organization's culture. Thus, the aim and objective of the present research are to explore the literature deeply and attempt to understand both organizational culture and ambidextrous innovation, along with key cultural aspects with regard to ambidexterity. The present research deeply dived into the model of organizational culture and attempted to build synergy between each model with respect to ambidexterity. The results of the present research suggest that Cameron and Quinn's competing value framework, once amalgamated with the Schein model, creates an organizational culture framework that can be used to develop a culture that is best suited to the implementation of ambidextrous innovation. The Schein model provides a comprehensive guideline for each value of the competing value framework. Further, the present research also extracted key insights with regard to the role culture can play in innovation in general and ambidextrous innovation in particular. Finally, the present research also attempted to build a list of culture enablers and inhibitors that can facilitate and impede the process of ambidextrous innovation.
Keywords: 350; ambidextrous innovation; conceptual framework; culture models; exploitation; exploration; organizational culture